Predictable Changes in Extreme Sea Levels and Coastal Flood Risk Due To Long‐Term Tidal Cycles. Issue 4 (30th March 2022) - Enríquez, Alejandra R.; Wahl, Thomas; Baranes, Hannah E.; Talke, Stefan A.; Orton, Philip M.; Booth, James F.; Haigh, Ivan D.
Abstract: We demonstrate that long‐term tidally induced changes in extreme sea levels affect estimates of major flood hazard in a predictable way. Long‐term variations in tides due to the 4.4 and 18.6‐year cycles influence extreme sea levels at 380 global tide gauges out of a total of 581 analyzed. Results show coherent regions where the amplitudes of the modulations are particularly relevant in the 100‐year return sea level, reaching more than 20 cm in some regions (western Europe, north Australia, and Singapore). We identify locations that are currently in a positive phase of the modulation and therefore at a higher risk of flooding, as well as when (year) the next peak of the long‐term tidal modulations is expected to occur. The timing of the peak of the modulation is spatially coherent and influenced by the relative importance of each cycle (4.4 or 18.6‐year) over the total amplitude. An evaluation of four locations suggests that the potentially flooded area in a 100‐year event can vary up to ∼45% (in Boston) as a result of the long‐term tidal cycles; however, the flooded area varies due to local topography and tidal characteristics (6%–13%). We conclude that tidally modulated changes in extreme sea levels can alter the potentially inundated area in a 100‐year event and that the traditional, fixed 100‐year floodplain is inadequate for describing coastal flood risk, even without considering sea‐level rise. Plain Language Summary: Interannual and decadal (long‐term) variations in tides modulate extreme sea levels, increasing the risk of flooding at specific and predictable times. Here, we use a data set of 581 tide gauges to estimate the magnitude of the long‐term tidally induced changes in extreme sea levels as well as to identify the timing of the peak of the modulations. We find significant amplitudes of the long‐term tidal modulations in extreme water levels. We conclude that the long‐term modulations in tides influence the total inundation area and, therefore, they should be taken into account when assessing coastal vulnerability. Key Points: Long‐term tidal cycles (4.4 and 18.6‐year) modulate extreme sea levels and affect estimates of flood risk The timing of the peak of both modulations is influenced by the relative importance of each cycle over the total amplitude Tidally induced changes in extreme sea levels affect estimates of total inundation area